Mixed breeding system in the hermaphroditic land slug Arion intermedius (Stylommatophora, Arionidae). Issue 4 (24th October 2013) - Jordaens, Kurt; Van Houtte, Natalie; Helsen, Philippe; Breugelmans, Karin; Jaksons, Peter; Backeljau, Thierry
<x xml:space="preserve">Abstract</x> Theory suggests that hermaphroditic plants and animals should be either entirely outcrossing or entirely selfing. As such, very few hermaphroditic plants and basommatophoran snails have a mixed breeding system. However, reliable estimates of selfing rates are lacking for most hermaphroditic animals. This partly prevents to delineate the relative contributions of the selective factors that determine selfing and outcrossing rates in hermaphroditic animal taxa. Here, we studied the population genetic structure of, and breeding system in, 11 populations of the hermaphroditic land slug Arion intermedius using five polymorphic microsatellite loci. Moreover, genotype frequencies deviated significantly from Hardy–Weinberg equilibrium expectations for most of the loci in all populations suggesting some level of selfing. Estimates of the selfing level s, suggest moderate levels of outcrossing (mean s based on FIS= 0.84; mean s based on the two‐locus heterozygosity disequilibrium = 0.20, or with a ML approach = 0.22). Our study therefore suggests that A. intermedius has a mixed breeding system. A re‐analysis of allozyme data from another arionid slug ( subgenus Carinarion) indicates that mixed breeding may be more common in arionid slugs than hitherto was assumed. These results seem therefore at variance with current theoretical and empirical predictions and opens perspectives for the study on the evolutionary factors driving mixed breeding systems in animals.